Edukasi Pencegahan Stunting Melalui Inovasi Olahan Es Krim Ubi: Pendekatan Participatory Action Research di Kelurahan Selomerto, Kabupaten Wonosobo - Rivaldo Rivaldo (JURNAL ILMIAH NUSANTARA, 2025)
Stunting remains a major health challenge in Indonesia, including in Selomerto Village, Wonosobo Regency. This study aims to increase public understanding of stunting prevention through the development of an innovative, attractive and nutritious sweet potato ice cream product. The study employed a Participatory Action Research method involving community health post (Posyandu) cadres, village officials, and community service students. The activity involved hands-on training in making sweet potato ice cream and health education related to stunting. The results showed an increase in public knowledge and awareness, particularly among mothers and Posyandu cadres, of the importance of providing balanced nutrition for children. The Cilembu sweet potato ice cream innovation has proven to be a healthy, child-friendly local food option, and has the potential to support government policies to reduce stunting rates. This simple, practice-based educational approach has the potential to be an effective strategy in increasing community participation in stunting prevention efforts.